2019
DOI: 10.4314/tjpr.v17i10.7
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical composition, and analgesic and antiinflammatory properties of essential oil of <i>Chamaemelum nobile</i> (Asteraceae L All) in rodents

Abstract: Purpose: To investigate the in vivo analgesic and anti-inflammatory activities of essential oil of dried flowers of Chamaemelum nobile (Asteraceae L. All) in Swiss mice and Wistar rats, respectively. Methods: The volatile oil of the dried flowers of C. nobile obtained by hydrodistillation was analyzed by gas chromatography-mass spectrometry (GC-MS). Animals were assigned to the following experimental groups: C. nobile (180 mg/kg), ibuprofen (100 mg/kg) and vehicle-treated groups. Chemical and thermal pain mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 13 publications
0
2
1
Order By: Relevance
“…Roozbeh and Dong-Jin (2017) [ 36 ] reported that EO from the same plant collected in Iran is characterized by Chamazulene (31.12%), β-Pinene (10.11%), ά-bisabolol (7.32%), a pigenin-7-glucoside (6.20%), ά-bisabololoxide A (5.98%), α-pinene (5.97%), and β–thujone (4.84%). Aremu et al (2018) [ 37 ] also showed a difference in the chemical composition of Chamaemelum nobile EO compared to our study, with alpha-bisabolol being the most abundant quantitatively (>50%). The second most abundant compound was farnesene (5.35%), followed by spathulenol (2.56%).…”
Section: Resultscontrasting
confidence: 51%
“…Roozbeh and Dong-Jin (2017) [ 36 ] reported that EO from the same plant collected in Iran is characterized by Chamazulene (31.12%), β-Pinene (10.11%), ά-bisabolol (7.32%), a pigenin-7-glucoside (6.20%), ά-bisabololoxide A (5.98%), α-pinene (5.97%), and β–thujone (4.84%). Aremu et al (2018) [ 37 ] also showed a difference in the chemical composition of Chamaemelum nobile EO compared to our study, with alpha-bisabolol being the most abundant quantitatively (>50%). The second most abundant compound was farnesene (5.35%), followed by spathulenol (2.56%).…”
Section: Resultscontrasting
confidence: 51%
“…Since ROS plays an important role in the pathogenesis of certain inflammatory diseases, natural antioxidants can scavenge ROS and improve the inflammatory state and consequently combat these disorders (31,32). Several studies have been carried out to prove the antiinflammatory effect of Chamaemelum nobile, including Olukayode et al (33) with an in vivo evaluation of the analgesic and anti-inflammatory effect of Roman chamomile essential oil (compared to ibuprofen). The latter had been used against inflammation found in the mouse paw.…”
Section: Discussionmentioning
confidence: 99%
“…112 Recently, the oral administration of EO from Roman chamomile reduced paw inflammation and exerted analgesic effects against thermal pain, corroborating the use of C. nobile in the treatment of inflammatory disorders. 113 Ps and EOs of Roman chamomile have been also reported to possess in vivo antiinflammatory effects. 110 C. nobile has been described to present cytotoxic effects against several cancer cell lines.…”
Section: Nobilementioning
confidence: 99%